Revision of the Chinese Macropelopia (Diptera: Chironomidae: Tanypodinae), with description of a new species - Tang, Hongqu; Niitsuma, Hiromi (Zootaxa, 2020)
The Chinese species of Macropelopia Thienemann are reviewed. A new species belonging to the subgenus Macropelopia, M. (M.) pergrandis sp. n., is described based on the adult male and pupa. Macropelopia grandivolsella Wang, Cheng et Wang and M. rotunda Wang, Cheng et Wang are synonymized with M. (M.) paranebulosa Fittkau and M. (M.) kibunensis (Tokunaga) respectively, based on reexamination of the type materials. Macropelopia galbina Wang, Cheng et Wang is transferred to the genus Brundiniella, and the male holotype is redescribed.